Optimal Pedestrian Path Planning in Evacuation Scenario - Kasanický, Tomáš; Zelenka, Ján (Computing and Informatics, 2015)
Simulation of evacuation plans is a relatively complex problem. It is necessary to simulate a number of separate processes which interact in the result. Namely, they are pedestrian-pedestrian interactions, pedestrian-static object (e.g. wall) interactions and pedestrian-environment (fire, smoke, etc.) interactions. In this case, the evacuation simulation is controled on the microscopic level. Microscopic level considers each individual separately and pedestrian is planning his/her path to the exit with regard to the above-mentioned interactions. In this article we focus on path planning during evacuation and describe algorithms applied in this area. At the end we propose a method of the space evaluation with linear time complexity and planned path compared with commercial software tools.